(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
A description of the front of a table tomb found under a pile of rubbish in the chancel of Abroath Abbey by Henry Laing. It was thought to be a fragment as only four of an estimated seven carved figures remained, and Laing called it’s style very fine, if not elaborate. From arms carved into the design, Laing deduces that the Abbot to whom the tomb was dedicated was Walter Paniter, to whom the building of the chapter house of the Abbey is ascribed. Laing also describes a ruined fragment of a figure that he surmises would have been the lid of the tomb, and the report says that an R.C. Bell made an engraving to show what it might have looked like. Meetings minutes for December 8, 1851 are appended.